2023
DOI: 10.1002/ajh.26852
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of patients with chronic myeloid leukemia treated with third‐line BCR::ABL1 tyrosine kinase inhibitors

Abstract: The BCR::ABL1 tyrosine kinase inhibitors (TKIs) have improved the outcomes of patients with chronic myeloid leukemia (CML). After failing second-generation TKI (2G-TKI), the optimal third-line therapy in chronic phase CML (CML-CP) is not well established. We analyzed 354 patients with CML-CP treated with a third-line BCR:: ABL1 TKI at our institution, and in the PACE and OPTIC trials, and evaluated the outcome after alternate 2G-TKIs or ponatinib. We performed a propensity score matching analysis to compare ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
10
0
4
Order By: Relevance
“…A retrospective analysis comparing the outcomes of patients with CML-CP treated with 2G TKIs or ponatinib as third-line TKI therapy found the 3-year PFS rate with ponatinib was 81% versus 60% with 2G-TKIs and the 3-year OS rate was 89% with ponatinib versus 81% with 2G TKIs; these survival outcomes were maintained after propensity matching [ 34 ]. Furthermore, third- or fourth-line ponatinib yielded response rates (≤1% BCR::ABL1 IS : PACE, 46% by 12 months and 54% by ~5 years; OPTIC, 52% by 12 months and 56% by 24 months) [ 4 , 19 , 21 ] comparable or better than those reported for second-line bosutinib (≤1% BCR::ABL1 IS , 46–50%) [ 35 ], suggesting ponatinib could be beneficial in the second-line setting.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis comparing the outcomes of patients with CML-CP treated with 2G TKIs or ponatinib as third-line TKI therapy found the 3-year PFS rate with ponatinib was 81% versus 60% with 2G-TKIs and the 3-year OS rate was 89% with ponatinib versus 81% with 2G TKIs; these survival outcomes were maintained after propensity matching [ 34 ]. Furthermore, third- or fourth-line ponatinib yielded response rates (≤1% BCR::ABL1 IS : PACE, 46% by 12 months and 54% by ~5 years; OPTIC, 52% by 12 months and 56% by 24 months) [ 4 , 19 , 21 ] comparable or better than those reported for second-line bosutinib (≤1% BCR::ABL1 IS , 46–50%) [ 35 ], suggesting ponatinib could be beneficial in the second-line setting.…”
Section: Discussionmentioning
confidence: 99%
“…Of 11 studies analyzed, the authors found that in 3L-TKI treatment the sequential use of 2GTKI was of limited value: the probability of CCyR was 22–26% compared to 60% in the ponatinib-treated patients. Similarly, a retrospective multicenter study comparing the efficacy of ponatinib versus 2GTKI in 3 L therapy in 354 CML patients, including also PACE [ 15 ] and OPTIC [ 16 ] participants, found that 3GTKI allowed a higher rate of deeper responses, longer PFS and OS and was the only independent factor associated with better survival in a propensity score matching analysis [ 17 ]. The efficacy of ≥3L-ponatinib after failure of 2GTKI was also shown by another recent sub-analysis of the PACE and OPTIC studies [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…9,54,56 This highlights the improved survival with ponatinib compared with second-generation TKIs in patients with resistant CML-CP. 52,[57][58][59] In contrast, with longer followup of the ASCEMBL trial in patients with CML-CP and $2 prior TKIs, no survival difference was noted between asciminib and bosutinib, with 2-year OS rates of 97% and 99%, respectively. 60 Treating patients with ponatinib or asciminib is expensive.…”
Section: Ponatinib and Asciminib: Third-generation Tkismentioning
confidence: 95%